Workplace Facilities, Organizational Differences, and Strategic Approaches to Enhancing Job Satisfaction: A Study of Public and Private Organizations in Bangalore City (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study looked at how Bangalore City's public and private businesses' workplace facilities affected workers' job satisfaction. Finding out how satisfied employees were with their workplace amenities, identifying any disparities among industries, and devising solutions were the objectives. 150 employees—75 from the public sector and 75 from the private sector were asked to complete a standardized questionnaire on a 5-point Likert scale. Descriptive statistics, independent samples T-test and reliability evaluations using SPSS were all used in the analysis. The findings indicated that public sector employees evaluated workplace facilities considerably more favorably than their private sector counterparts, suggesting superior infrastructure and organizational support within the public sector. However, overall job satisfaction did not differ significantly across the two sectors, indicating that elements outside workplace amenities, such as career advancement and organizational culture, also significantly influence satisfaction. These results show that private companies need to improve their physical and technological resources, whereas public companies should focus on ways to help employees career advancement and thrive. The study offers valuable insights for human resource managers and policymakers to improve employee happiness and organizational efficacy.